Inclusive Education for Lowvision Students at Magelang District Elementary School - Azka, Nidya Anscalia; Munirrahayu, Luluk; Wardana, Aditia Eska (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
This research was conducted at SDN Mendut 1 Mungkid Subdistrict, Magelang Regency with the aim of conducting research related to the implementation of inclusive education in Mendut State Elementary School against low vision students. While data collection techniques include: observations, interviews, and documents. The subjects of the study were 4th grade teachers, 5th grade teachers, and 6th grade teachers. Data analysis with the stages of collecting data, reducing, presenting data, conclusions, and verification. The results of this study showed that: there are 2 students abk namely deaf and low vision. ABK students can take lessons applied at SDN Mendut. SDN Mendut is said to have succeeded in educating ABK students as evidenced by ABK students who excelled in academic and non-academic. For example, in the classroom, they include students who excel in the classroom. Not only academic achievements, even they also participated in the race held in subdistricts and districts. Abk students in SDN Mendut have a high spirit to study, even they do not feel excluded and do not feel different from other students.